Prevalence of Gallstone Disease in Patients with Type 2 Diabetes in Port Harcourt, Nigeria: A Cross-Sectional Ultrasound Study - Aghedo, Kawa L; Ugboma, Enighe (British Journal of Healthcare and Medical Research, 2024)
Background: Diabetes mellitus (DM) and gallstone disease pose a significant global health burden. Type 2 diabetes mellitus (T2DM) increases the risk of gallstones; however, regional data are limited. Objectives: To compare gallstone prevalence between T2DM patients and non-diabetic controls at a Nigerian hospital and determine the associated factors. Methods: This cross-sectional study included 108 T2DM patients and 108 age-matched controls who underwent abdominal ultrasonography to identify gallstones. Demographic and clinical data were collected. Bivariate and multivariate analyses were used to evaluate relationships. Results: Gallstones were more prevalent in patients with T2DM (20.4%) than in controls (9.3%, p=0.0022). T2DM was associated with 2.5× higher odds of gallstones after adjustment. Higher gallstone rates were observed in older T2DM patients (p=0.05) but not by sex. A longer T2DM duration and greater body mass index independently predicted gallstones (p<0.05). Most T2DM patients (88.9%) lacked knowledge of gallstones. Conclusion: T2DM significantly increased the gallstone risk in the Nigerian cohort. Modifiable risk factors, including obesity and glycemic control, warrant targeted screening and interventions. Knowledge gaps highlight the need for patient education on diabetes complications. Regional epidemiological data can guide tailored management strategies to reduce gallstone-related morbidities in high-risk populations.